2017
DOI: 10.1021/acsphotonics.7b01217
|View full text |Cite
|
Sign up to set email alerts
|

Beam Steering with Dielectric Metalattices

Abstract: We study optical wave manipulations through high-index dielectric metalattices in both diffractionless metasurface and diffractive metagrating regimes. It is shown that the collective lattice couplings can be employed to tune the excitation efficiencies of all electric and magnetic multipoles of various orders supported by each particle within the metalattice. The interferences of those adjusted multipoles lead to highly asymmetric angular scattering patterns that are totally different from those of isolated p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 72 publications
1
72
0
Order By: Relevance
“…6(a), where a metalattice of Si nanodisks can fully reflect the incident wave with resonant ED or MD modes within each unit cell. Similar effect can be achieved with the higher-order multipoles [24,118], where quadrupole and/or octupole resonances (or their combinations with ED and MD modes) can also result in full wave reflection. Perfect reflection can be further categorized based on the phase (relative to the incident wave) of the reflected waves, which are highly related to the recent studies of electric and magnetic mirrors [24, 125,126].…”
Section: Perfect Reflectionmentioning
confidence: 66%
See 3 more Smart Citations
“…6(a), where a metalattice of Si nanodisks can fully reflect the incident wave with resonant ED or MD modes within each unit cell. Similar effect can be achieved with the higher-order multipoles [24,118], where quadrupole and/or octupole resonances (or their combinations with ED and MD modes) can also result in full wave reflection. Perfect reflection can be further categorized based on the phase (relative to the incident wave) of the reflected waves, which are highly related to the recent studies of electric and magnetic mirrors [24, 125,126].…”
Section: Perfect Reflectionmentioning
confidence: 66%
“…This is induced by the specific scattering patterns of the lattice cylinders [upper row in (d, e)], which originate from interferences of multipoles of different orders [lower row in (d, e); it agrees with the upper row that the dipolar approximation (dashed curves) is not sufficient here and higher-order multipoles should be taken into consideration]. Adapted from[118,134].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…After having thoroughly surveyed the hidden landscapes of electromagnetic multipoles of complex vectorial natures, now we aim to show how their topological properties could be wielded to bring new frames of visions. It is previously shown that periodic photonic structures could be treated in a reductionist manner: the far-field properties of the radiative Bloch modes are decided only by the multipolar radiations of unit-cells along the corresponding directions of open out-coupling channels [15,46,47]. For example, the coincidence of V-points of unit-cell radiations with the open channels would immediately produce BICs, as there is no effective energy leakage [15,16].…”
Section: (A)mentioning
confidence: 99%